2020
DOI: 10.1002/mma.6409
|View full text |Cite
|
Sign up to set email alerts
|

3D Rayleigh‐Bénard‐type natural convection in MWCNT‐nanofluid‐filled L‐shaped enclosures with consideration of aggregation effect

Abstract: Rayleigh‐Bénard type convective heat transfer in a 3D L‐shaped enclosure filled with multiwalled carbon nanotube (MWCNT)‐water nanofluids has been studied. The governing equations have been written using the vorticity‐vector potential formalism and solved based on the finite volume method (FVM). The simulations were performed for various values of Rayleigh number, aspect ratio, and MWCNT volume fraction. The aggregation effect was considered, and the viscosity and thermal cavity were evaluated accordingly to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Mahanthesh et al 11 studied the nanofluid flow under the impact of heat source, cross diffusion, and exponential space. The entropy generation between two rotating disks of CNTs nanofluid flow in the presence of thermal radiation and MHD was examined by Hosseinzadeh et al 12 Chamka and Djezzar, 13 Reddy et al, 14 and Almeshaal et al 15 have studied the CNTs Water nanofluid using various mathematical models for the enhancement of heat transfer analysis. Several other valuable scholars' articles have been available in literature that can be mentioned to references [16][17][18] for additional study.…”
Section: Introductionmentioning
confidence: 99%
“…Mahanthesh et al 11 studied the nanofluid flow under the impact of heat source, cross diffusion, and exponential space. The entropy generation between two rotating disks of CNTs nanofluid flow in the presence of thermal radiation and MHD was examined by Hosseinzadeh et al 12 Chamka and Djezzar, 13 Reddy et al, 14 and Almeshaal et al 15 have studied the CNTs Water nanofluid using various mathematical models for the enhancement of heat transfer analysis. Several other valuable scholars' articles have been available in literature that can be mentioned to references [16][17][18] for additional study.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the combination of these non-destructive techniques allows a noticeable enhancement of the heat transfer. Almeshaal et al (2020a) considered the aggregation effect on the Rayleigh-Bénard free convection in an L-shaped enclosure. The authors mentioned that the addition of the nanotubes influences the flow and temperature fields.…”
Section: Introductionmentioning
confidence: 99%
“…In general it is not appropriate to directly utilize the single-phase CNT nanofillers in high-sensitivity sensors. A small amount of CNT nanofillers are often added into the polymer matrix to make the functional nanocomposites [11,12]. This class of nanocomposites can possess excellent electrical properties while maintaining the flexibility [13].…”
Section: Introductionmentioning
confidence: 99%